Quasi-two-dimensional carriers in dilute-magnetic-semiconductor quantum wells under in-plane magnetic field - Simserides, C.; Galanakis, I. (Physica E: Low-Dimensional Systems and Nanostructures, 2008)
Due to the competition between spatial and magnetic confinement, the density of states (DOS) of a quasi-two-dimensional system deviates from the ideal step-like form both quantitatively and qualitatively. We study how this affects the spin-subband populations and the spin polarization as functions of the temperature, T, and the in-plane magnetic field, B, for narrow to wide dilute-magnetic-semiconductor quantum wells (QWs). We focus on the QW width, the magnitude of the spin–spin exchange interaction, and the sheet carrier concentration dependence. We look for ranges where the system is completely spin polarized. Increasing T, the carrier spin splitting, U0σ, decreases, while on increasing B, U0σ increases. Moreover, due to the DOS modification, all energetically higher subbands become gradually depopulated.